Discretionary Decision-Making in Constituency Offices: A New (Political) Front-Line of Canadian Immigration Processing - Marriott, Sarah (Université d'Ottawa / University of Ottawa, 2018)
Despite Canada’s reputation as a welcoming host-country, changes to immigration processing in the past twenty years have increasingly forced frustrated immigration applicants to seek assistance at their MP’s constituency office (MacLeod 2005). Due to an indirect decentralization of some aspects of immigration processing towards these offices, this immigration casework now accounts for 60 to 80% of urban MPs’ offices’ work (Rana 2016b). Despite this volume, and the documented importance of studying the discretionary decision-making practices of other actors in the immigration processing system (Bouchard & Wake Carroll 2002; Satzewich 2015a), the literature has never before considered constituency offices’ role in the Canadian immigration system. Thus, how do constituency assistants (CAs) exercise discretion in their immigration casework activities? And what variables influence this discretion? This dissertation draws on a qualitative analysis of semi-structured interviews with 15 current and former CAs in four provinces. We find that CAs’ discretion is not bounded to the same degree by official procedures or standards as in the immigration bureaucracy. Rather, CAs discretion leads to significant variations in service provision from office to office and even within offices. Furthermore, these variations stem from the influence of variables that would be considered inappropriate in the bureaucracy: CAs’ micro-level discretion rooted in their personal characteristics (Satzewich 2015a), and electoral considerations. CAs’ ‘flexibility’ can be seen as a necessary response to an unresponsive bureaucracy, but also highlights the politicization of immigration applications going through these offices, and raises important equity issues around access to the immigration bureaucracy in Canada.
Keywords: Constituency offices; Immigration; Discretion; Canadian politics; Bureaucracy; Canada; Member of Parliament; MP